Current State of Tax Audit Research In the Last Decade: A Bibliometric Review - Wati, Eny Gangga; Tjaraka, Heru (Amkop Management Accounting Review (AMAR), 2026)
This study analyzes tax audit literature from 2015 to 2025 to understand global research developments. This topic is important because tax audits play a central role in improving compliance, suppressing tax evasion, and strengthening fiscal justice. Using bibliometric methods, this study utilized 297 articles from 130 Scopus-indexed journals, including an overview, trends & contributors, articles & authors, network analysis, thematic maps, and the evolution of themes in tax audit research. The results show a significant publication rate of 16.23% per year, dominated by developed countries, and a shift in research focus from administrative aspects to strategic governance. Key themes identified include tax enforcement, tax compliance, and corporate governance. The evolution of tax audit research has now shifted its focus from administrative aspects to a multidisciplinary strategic approach. These findings are important for strengthening fiscal policy and increasing the effectiveness of tax audits.